1969
DOI: 10.1177/003072706900600104
|View full text |Cite
|
Sign up to set email alerts
|

Selenium in animal nutrition

Abstract: Only in recent years has the significance of selenium in animal nutrition been acknowledged. Deficiency of the element in the nutrition of ruminants is now known to be associated with certain muscular dystrophy conditions. In Australia these conditions occur more frequently in high rainfall areas and on soils originating in non-sedimentary rocks. They would appear to have been aggravated by certain pasture improvement techniques and by intensive husbandry. Nowadays they are yielding to control by various metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1971
1971
1997
1997

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 1 publication
1
21
0
Order By: Relevance
“…One area of research has been concerned with the minimal Se concentration required in the diet to prevent WMD (1,9,10,11,18). Results from studies in this research area indicate that the critical deficiency level in the diet is actually a range from 0.03 to 0.07 ppm, depending upon the vitamin E level and other factors.…”
Section: Effect Of Phosphorus Fertilization On the Selenium Concentramentioning
confidence: 99%
“…One area of research has been concerned with the minimal Se concentration required in the diet to prevent WMD (1,9,10,11,18). Results from studies in this research area indicate that the critical deficiency level in the diet is actually a range from 0.03 to 0.07 ppm, depending upon the vitamin E level and other factors.…”
Section: Effect Of Phosphorus Fertilization On the Selenium Concentramentioning
confidence: 99%
“…Nutrient interaction studies conducted on Se-rich agriculture soils, for example, have shown that excessive use of phosphorus fertilizers increases Se concentrations in forage plants to levels potentially toxic for Downloaded by [University of California Santa Barbara] at 06:07 10 June 2016 cattle and sheep [14,15,16]. However, the reported effects of P on Se uptake are inconsistent with one another [17,18]. Finding the best P levels for maximizing mustard's Se uptake may be critical for managing Se removal in high-concentration areas.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of selenium and vitamin E in bringing about a remission in gross calcification was noted in this work, but no study was made of the significance of calcium deposition in the early stages of the disease. Later reports from New Zealand (Andrews et al 1968) and Australia (Gardiner 1969) refer to calcification and recognize it as a feature in the overall pathology.…”
Section: Introductionmentioning
confidence: 99%